2008
DOI: 10.1093/carcin/bgn219
|View full text |Cite
|
Sign up to set email alerts
|

Ligand activation of peroxisome proliferator-activated receptor β/δ (PPARβ/δ) inhibits chemically induced skin tumorigenesis

Abstract: Peroxisome proliferator-activated receptor (PPAR)beta/delta-null mice exhibit enhanced tumorigenesis in a two-stage chemical carcinogenesis model as compared with wild-type mice. Previous work showed that ligand activation of PPARbeta/delta induces terminal differentiation and inhibits proliferation of primary keratinocytes, and this effect does not occur in the absence of PPARbeta/delta expression. In the present studies, the effect of ligand activation of PPARbeta/delta on skin tumorigenesis was examined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
70
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(83 citation statements)
references
References 49 publications
13
70
0
Order By: Relevance
“…Previous work demonstrated that activation of PPAR␤/␦ attenuated skin tumorigenesis in a 2-stage chemical carcinogenesis bioassay and inhibited proliferation of cells with a mutation in the Hras gene (3). This suggests that PPAR␤/␦ could inhibit tumorigenesis through inhibition of oncogenic Hras signaling, which was examined in these studies.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…Previous work demonstrated that activation of PPAR␤/␦ attenuated skin tumorigenesis in a 2-stage chemical carcinogenesis bioassay and inhibited proliferation of cells with a mutation in the Hras gene (3). This suggests that PPAR␤/␦ could inhibit tumorigenesis through inhibition of oncogenic Hras signaling, which was examined in these studies.…”
mentioning
confidence: 80%
“…Consistent with this phenotype, exacerbated skin tumorigenesis was also found in Ppar␤/␦-null mice following a two-stage chemical carcinogenesis bioassay (31). Subsequent studies demonstrated that ligand activation of PPAR␤/␦ inhibits chemically induced tumorigenesis (3,4,68). One mechanism that may underlie these PPAR␤/␦-dependent chemopreventive effects is modulation of epidermal cell proliferation through inhibition of protein kinase C ␣/mitogen-activated protein kinase (PKC␣/MAPK) (31,33).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…It is possible that this dual action also explains the different results concerning the influence of PPAR␦ activators in the treatment and development of various tumor entities. Recently, Bility et al demonstrated that PPAR␦ agonists inhibit chemically induced skin carcinogenesis, whereas Kim et al demonstrated that chemically induced skin carcinogenesis is not influenced by PPAR␦ (29,30). Han et al demonstrated that PPAR␦ agonists induce human lung cancer cell proliferation, whereas He et al found that they do not influence lung cancer cell proliferation (31,32).…”
Section: Discussionmentioning
confidence: 99%